2012
DOI: 10.1186/1747-597x-7-33
|View full text |Cite
|
Sign up to set email alerts
|

High risk alcohol-related trauma among the Aboriginal and Torres Strait Islanders in the Northern Territory

Abstract: High risk drinking is linked with high rates of physical harm. The reported incidence of alcohol - related trauma among Aboriginal and Torres Strait Islander people in the Northern Territory is the highest in the world. Facial fractures are common among young Aboriginal and Torres Strait Islanders. They are often linked with misuse of alcohol in the Northern Territory and are frequently secondary to assault. This review focuses on alcohol-related trauma in the Territory and draws attention to an urgent need fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
22
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 22 publications
(23 citation statements)
references
References 37 publications
(38 reference statements)
1
22
0
Order By: Relevance
“…As per the Health and Welfare of Australia's Aboriginal and Torres Strait Islander People's report, high risk alcohol consumption was estimated based on the largest quantity of alcohol consumed in a single day during a fortnight (Australian Bureau of Statistics [ABS], 2013). Indigenous alcohol abuse is also highly prevalent in Australia (ABS, 2010;Chikritzhs, Heale, & Webb, 2000;Chikritzhs & Pascal, 2004), New Zealand (''About Indigenous People, '' 2007;National Drug Strategy, 2001), and Canada (ABS, 2013). Alcohol abuse was noted to be highest among Native American or Alaska Natives in the 12 to 17 years age group in 2000.…”
Section: Introductionmentioning
confidence: 98%
“…As per the Health and Welfare of Australia's Aboriginal and Torres Strait Islander People's report, high risk alcohol consumption was estimated based on the largest quantity of alcohol consumed in a single day during a fortnight (Australian Bureau of Statistics [ABS], 2013). Indigenous alcohol abuse is also highly prevalent in Australia (ABS, 2010;Chikritzhs, Heale, & Webb, 2000;Chikritzhs & Pascal, 2004), New Zealand (''About Indigenous People, '' 2007;National Drug Strategy, 2001), and Canada (ABS, 2013). Alcohol abuse was noted to be highest among Native American or Alaska Natives in the 12 to 17 years age group in 2000.…”
Section: Introductionmentioning
confidence: 98%
“…Further, it has been reported that most of the assaults against women in remote NT communities are perpetrated by a drunken husband or other family member. Alcohol-related facial trauma is common, with an estimated 350 cases per year admitted to the Maxillofacial Surgery Unit of the Royal Darwin Hospital (RDH) [11,12]. Many of these admissions, approximately 80% are of Indigenous people [12].…”
Section: Introductionmentioning
confidence: 99%
“…Alcohol-related facial trauma is common, with an estimated 350 cases per year admitted to the Maxillofacial Surgery Unit of the Royal Darwin Hospital (RDH) [11,12]. Many of these admissions, approximately 80% are of Indigenous people [12]. Therefore, there is an urgent need for an effective and culturally appropriate intervention to address binge drinking and alcohol-related harm in this group.…”
Section: Introductionmentioning
confidence: 99%
“…A particular focus of alcohol-related violence involves mandibular fractures [20]. Facial fractures in the NT are close to 120 per 100,000 of population, and in Indigenous people occur at a massive 155 per 100,000 [21].…”
Section: Introductionmentioning
confidence: 99%
“…While there is abundant evidence that brief interventions are effective in the treatment of high-risk drinking [27], there is less research on the impact of brief interventions on alcohol-related violence [20]. …”
Section: Introductionmentioning
confidence: 99%